I have a dream: School principals as entrepreneurs. (July 2015) - Yemini, Miri; Addi-Raccah, Audrey; Katarivas, Keren
Most policymakers and academics agree that entrepreneurship is indispensable to society's development and well-being. Fostering entrepreneurship has become a matter of highest priority in public policy worldwide. Given the growing pressures of decentralization and competitiveness that schools have faced over the last 20 years, the role of school principals as entrepreneurs is receiving growing interest in academic and practical contexts. Our study examines school principals from the perspective of their schools' entrepreneurship. Accordingly, we seek to reveal the meaning of entrepreneurship in school settings and to examine the conditions that are related with school principals' entrepreneurial activities. This study examines 10 school principals of different educational streams in Israel, who have been identified as entrepreneurs by their peers and supervision authorities. We characterize these agents of change as institutional entrepreneurs and present their motives and resources that facilitate their entrepreneurship in school settings. We include several novel parameters that may be applied to characterize school entrepreneurship, with an emphasis on institutional lens. This study contributes to the broader educational literature that addresses school principals' roles within a decentralized system demanding high accountability.